2001
DOI: 10.1128/jvi.75.11.5009-5017.2001
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Nuclear Ribonucleoprotein A1 Binds to the 3′-Untranslated Region and Mediates Potential 5′-3′-End Cross Talks of Mouse Hepatitis Virus RNA

Abstract: The genome of mouse hepatitis virus (MHV) is a singlestranded, linear, positive-sense, polyadenylated RNA of approximately 31 kb in length (22,24,39). All of the viral proteins are translated from subgenomic mRNAs, except those encoded by the first open reading frame, which are translated from the genome-sized RNA. In MHV-infected cells, six or seven subgenomic mRNAs are transcribed, all of which contain a common leader sequence derived from the 5Ј end of the genome, as well as a common 3Ј end including a 302-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
101
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(106 citation statements)
references
References 54 publications
(84 reference statements)
3
101
1
1
Order By: Relevance
“…The 5Ј UTR, critical in replication, transcription, and translation (24), was shown to possess only 93.2% nucleotide identity to LV, yet the 3Ј UTR sequence was accurately maintained (98.2% identity). The reason for this disparity is unknown, as evidence suggests that these two regions may be in close proximity during viral replication (23,49). NSP2 has been reported to be the most variable part of the genome (11,61), and the ORF 1a sequence of EuroPRRSV was consistent with that notion, displaying a 17-aa deletion within the NSP2 protein, the only deletion or insertion observed in relation to the LV genomic sequence.…”
Section: Discussionsupporting
confidence: 63%
“…The 5Ј UTR, critical in replication, transcription, and translation (24), was shown to possess only 93.2% nucleotide identity to LV, yet the 3Ј UTR sequence was accurately maintained (98.2% identity). The reason for this disparity is unknown, as evidence suggests that these two regions may be in close proximity during viral replication (23,49). NSP2 has been reported to be the most variable part of the genome (11,61), and the ORF 1a sequence of EuroPRRSV was consistent with that notion, displaying a 17-aa deletion within the NSP2 protein, the only deletion or insertion observed in relation to the LV genomic sequence.…”
Section: Discussionsupporting
confidence: 63%
“…33,34 Such interaction is likely mediated by several host cell proteins, such as poly-(A)-binding protein, an important trans-acting factor required for viral translation and replication. 10 Thus, targeting the terminus of 3 0 UTR by AS-7 will interfere with 5 0 -and 3 0 -UTR end interactions of viral RNA, which in turn inhibit viral transcription and translation. The data reported here have confirmed that AS-7 confers specific activity in both cardiomyocytes and in the mouse model wherein the pathophysiological conditions are much closer to a clinical environment.…”
Section: Inhibition Of Cvb3 Replication By As-odn J Yuan Et Almentioning
confidence: 99%
“…9 Therefore, efficient blocking of the 3 0 terminal region of CVB3 RNA may inhibit the binding of cellular translation or transcription initiation factors, thereby preventing the formation of a replication unit of a circular viral RNA. 10 The potential of oligodeoxynucleotides to act as antisense agents that inhibit the replication of the Rous sarcoma virus was discovered in 1978. 11 As a novel class of therapeutic agents to selectively block or inhibit gene expression, antisense oligodeoxynucleotides (AS-ODNs) have attracted great interest in the development of drugs and gene functional studies.…”
mentioning
confidence: 99%
“…Given that anti-hnRNP A1 and anti-PCBP2 were able to reduce complex formation and that both proteins bind to the MNV-1 genomic RNA and have been implicated in the stabilization of viral RNA-RNA interactions (27,49), we next examined if these proteins could promote the interaction of the 5= and the 3= ends of the MNV-1 genomic RNA. Therefore, a coprecipitation assay was performed using biotin-labeled 5=-end and ␣-32 P-labeled 3=-UTR RNA probes in the presence of both PCBP2-His and His-hnRNP A1 recombinant proteins (Fig.…”
Section: Resultsmentioning
confidence: 99%